CRAFTPy: allowing people with visual impairments to create diagrams - Fraga, Lucas Lopes; Santos, Rafael Tosta; Rocha, Larissa (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3564, 2024)
The inclusion of students with visual impairments (SVI) in higher education has greatly advanced with the advent of newtechnologies. Despite these strides, challenges remain, particularly in Information and Communication Technology (ICT) courses that heavily rely on visual elements. Screen readers facilitate SVI’s access to digital content, but many educational tools are still incompatible with these readers. This incompatibility is especially problematic in tools requiring interaction with visual components, such as block-based programming, diagramming, and 3D modeling tools. This study introduces CraftPy, an accessible web tool fully compatible with screen readers. CraftPy enables SVI to create various types of diagrams using Python code, employing an object-oriented approach to design classes, actors, entities, attributes, and relationships. We also conducted a preliminary evaluation involving eight SVI participants to assess the tool’s effectiveness. Overall, participants found the tool to be highly accessible with screen readers and user-friendly. They were able to complete the experiment tasks with minimal difficulties. However, improvements are needed, particularly in enhancing screen responsiveness for low-vision users who depend on screen magnifiers. By developing CraftPy, we aim to promote equity in higher education, offering SVI enhanced opportunities to succeed in ICT courses. Link to the video:  https://youtu.be/NXu4xbOH8Q4